2005
DOI: 10.1007/s11177-005-0010-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mitochondrial DNA variation in the population of oroks

Abstract: Mitochondrial DNA (mtDNA) variation was studied in population of Oroks ( N = 61), the indigenous inhabitants of Eastern Siberia. Most of the mtDNA types examined fell into five haplogroups (C, D, G, M10, and Y) typical of Eastern Eurasian populations. For three haplogroups (D, C, and M10), the founder effect was established. In one individual, a unique lineage belonging to haplogroup HV and typical of Caucasoids was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…In Europe, the dense and extensive sampling of the HVR-I diversity has revealed extremely low frequencies of hg C1, with very few haplotypes found in Germans [14], Canarians [15], Icelanders [16][17] and Bashkirs [18] (Figure 2). These sequences lack HVR-I Single Nucleotide Polymorphisms (SNPs) diagnostic of the sub-clades C1a (T16356C) and C1d (A16051G).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, the dense and extensive sampling of the HVR-I diversity has revealed extremely low frequencies of hg C1, with very few haplotypes found in Germans [14], Canarians [15], Icelanders [16][17] and Bashkirs [18] (Figure 2). These sequences lack HVR-I Single Nucleotide Polymorphisms (SNPs) diagnostic of the sub-clades C1a (T16356C) and C1d (A16051G).…”
Section: Introductionmentioning
confidence: 99%
“…We found six haplotypes from haplogroups C, D4 and M10 (Table 1). Haplogroup D4 has a high distribution frequency (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).3%) in northern Asians 7,8 and eastern Asians. 9 Haplogroup C has a very high distribution frequency (15.9-67.2%) in Siberia, 7 but a low frequency in China (3.5%).…”
Section: Resultsmentioning
confidence: 99%
“…9 Haplogroup M10 is a new subhaplogroup of M 10 with a frequency range of 0-2.3% in modern Han Chinese, 11 while a few M10 individuals have also been found among Mongolians and Yakuts. 8,12 A phylogenetic tree was constructed to determine the genetic relationship between the ancient Pengyang people and related populations ( Figure 2). In haplogroup C, the Han Chinese originating from the farming people 1,9,10 are concentrated in one group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same may be true for the low genetic diversities found in most southeast Siberian populations compared with East Asian populations (Table 3). Anthropologically, the Udegeys are characterized by a complex of morphological traits typical of the Mongolians and/or Baikal type, which bring them close to Evens, Evenki, Manchurians, and Negidalts (Smolyak, 1975;Crawford et al, 2002;Bermisheva et al, 2005). It has also been widely suggested that they have migrated to the territories of the Amur River basin from an area around Lake Baikal in south Siberia (Smolyak, 1975;Alexeev and Gohman, 1984).…”
Section: Resultsmentioning
confidence: 99%